HUKUM, EKONOMI DAN KESEJAHTERAAN: Telaah Yuridis atas Dinamika Pengaturan dan Implementasi Pasal 33 UUD 1945 - Basuki, Udiyo (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
The emergence of a school economic in the world will always be associatedwith the school of economic that have developed previously, so is thepattern of the Indonesian economy. Fierce struggle of capitalism andsocialism gives a significant influence toward Indonesian economicideology. Pancasila as the foundation of economic nation, through thedialectical process raises three kinds of terms that is the constitution ofthe economy, the economic constitution, and economic Pancasila, the three have the same phrase with a different meaning. The idea of democracy in economy are listed in UUD 1945 Article 33 paragraph (4) does contain the idea of political democracy as well as economic democracy.That is, the highest authority of the State of Indonesia is the people,both in the field of politics or the economy. Indonesia which has moregive priority to economic growth from economic equality appears to havedifficult times, the economic crisis experienced since mid-2007 has beena fundamental component of economic meluluhlantahkan until economicgrowth rate for 2008 was measured with a minus sign. This conditionindicates that since the signing of the 21st century, Indonesia is notready to face the era of free trade.